Composite materials science and engineering - Chawla, Krishan K. 1942- (Springer, 2019)
The fourth edition of Krishan Chawla's widely used textbook, Composite Materials, offers integrated and completely up-to-date coverage of composite materials. The book focuses on the triad of processing, structure, and properties, while providing a well-balanced treatment of the materials science and mechanics of composites. In this edition of Composite Materials, revised and updated throughout, increasing use of composites in industry (especially aerospace and energy) and new developments in the field are highlighted. New material on the advances in non-conventional composites (which covers polymer, metal and ceramic matrix nanocomposites), self-healing composites, self-reinforced composites, biocomposites and laminates made of metals and polymer matrix composites is included. Examples of practical applications in various fields are provided throughout the book, with extensive references to the literature. The book is intended for use in graduate and upper-division undergraduate courses and as a reference for the practicing engineers and researchers in industry and academia
Keywords: Ceramics; Glass; Composites (Materials); Composite materials; Engineering design; Polymers; Civil engineering; Materials science; Verbundwerkstoff; Hardcover, Softcover / Technik/Maschinenbau, Fertigungstechnik